(untitled) (Research, Society and Development, 2024)
The rapid growth of blockchain technology, alongside the rise of the first cryptocurrency, Bitcoin, has significantly influenced the financial market, giving birth to new investment opportunities, including Non-Fungible Tokens (NFTs). This study aims to investigate the key factors influencing the pricing of NFTs and the impact of investor subjectivity on this process. Through an extensive literature review and qualitative research involving active NFT investors, the study reveals that emotional factors such as speculation and euphoria significantly impact NFT pricing, highlighting the short-term volatility of the market. Cognitive biases like Fear of Missing Out and loss aversion are also prevalent among investors, although experienced investors generally manage to avoid acting on these biases. The study further identifies that despite the speculative nature of NFTs, investors strive for rational and objective analysis, focusing on risk-return asymmetry and market reception. However, opinions on the solidity of NFTs as long-term investments are divided, indicating a significant uncertainty regarding their viability for long-term holding.